Sistem Data Bridge Pemantauan Gunungapi Berbasis Application Protocol Interface (Studi Kasus di Provinsi Jawa Barat) - Rudi Kurniawan; Hamdan Hanafi (Jurnal ICT: Information Communication & Technology, 2022)
The state of Indonesia has around 127 active volcanoes spread over a 7-kilometer long volcanic route, and this route is a disaster-prone area. Where in the area there are approximately 4 million people who live and enter in disaster-prone areas. Therefore, the Center for Volcanology and Geological Hazard Mitigation (PVMBG) of the Geological Agency of the Ministry of Energy and Mineral Resources (ESDM) continues to carry out 24-hour surveillance of active volcanoes so that if an eruption occurs, it can be anticipated. Communities who live around volcanic routes are in areas that are less safe, because the threat of a volcanic disaster can come suddenly so that people may be in an unprepared state when a disaster or volcanic eruption occurs. Ignorance of information about volcanic conditions by the community is an important problem that must be solved. This research study is about the state of volcanoes in the province of West Java with the aim of creating a system that can be used to obtain complete information about the volcano. The research methodology and data collection techniques are through literature studies and interviews. Agile methodologies are used in developing systems or applications. The data bridge system is an API that can be consumed by the frontend (website), the frontend can take advantage of the existing APIs in the data bridge system to get complete information about volcanoes. The author makes a data bridge API (Application Protocol Interface) system using the REST API architecture to communicate and uses the Go programming language as the main engine. The data bridge system displays complete information about volcanoes communicating or consuming data from two services (third party), the two services are the PVMBG API service and the BMKG API service. With the data bridge system, it is hoped that it can be a solution to solve the problem of the lack of information about volcanoes in Indonesia. The target is that the public can find it easy to find and view information about volcanoes so that there can be early prevention when a disaster is about to occur in the form of a volcanic eruption or other things